Incorporation of Thymidine Analogs for Studying Replication Kinetics in Fission Yeast - Rhind, Nicholas (2009)
SUMMARY: Labeling DNA during in vivo replication by the incorporation of exogenous thymidine and thymidine analogs has been a mainstay of DNA replication and repair studies for decades. Unfortunately, thymidine labeling does not work in fungi, because they lack the thymidine salvage pathway required for uptake of exogenous thymidine. This obstacle to thymidine labeling has been overcome in yeast by engineering a minimal thymidine salvage pathway consisting of a nucleoside transporter to allow uptake of exogenous thymidine from the medium and a thymidine kinase to phosphorylate the thymidine into thymidine monophosphate, which can be used by the cell. This chapter describes the labeling of fission yeast, Schizosaccharomyces pombe , with the thymidine analog BrdU in order to identify sites and determine kinetics of DNA replication.